Analisis Family-Type Board Game Menggunakan Kerangka MDA Untuk Perancangan Media Pengenalan Desain Produk - Claritza Nathania Setiadi; Guguh Sujatmiko; Hedi Cintya (Serat Rupa: Journal of Design, 2026)
The product designer profession plays an important role in the creative industry; however, interest among younger generations remains relatively low. An engaging and accessible medium is needed to introduce the complexity of this profession to high school students. This study analyzes family-type board games using the MDA (Mechanics, Dynamics, Aesthetics) framework as a foundation for designing an introductory educational medium for product design. A qualitative approach was employed through observational analysis of occupation-themed board games. The study identifies mechanics, dynamics, and aesthetic during gameplay. The findings indicate that resource management and progressive development mechanics effectively simulate real-world work processes. Dynamics such as action planning and resource counting foster strategic decision-making, while strong thematic integration enhances immersion and supports understanding of the represented profession. These findings provide a conceptual basis for designing board games as educational media to introduce the product designer profession to high school students.